Changes in kidney function among Nicaraguan sugarcane workers. (September 2015) - Laws, Rebecca L.; Brooks, Daniel R.; Amador, Juan José; Weiner, Daniel E.; Kaufman, James S.; Ramírez-Rubio, Oriana; Riefkohl, Alejandro; Scammell, Madeleine K.; López-Pilarte, Damaris; Sánchez, José Marcel; Parikh, Chirag R.; McClean, Michael D.
Abstract : Background: There is an epidemic of chronic kidney disease (CKD) of unknown etiology in Central American workers. Objectives: To investigate changes and job-specific differences in kidney function over a 6-month sugarcane harvest season, explore the potential role of hydration, and measure proteinuria. Methods: We recruited 284 Nicaraguan sugarcane workers performing seven distinct tasks. We measured urine albumin and serum creatinine and estimated glomerular filtration rate (eGFR). Results: eGFR varied by job and decreased during the harvest in seed cutters (−8·6 ml/min/1·73 m 2 ), irrigators (−7·4 ml/min/1·73 m 2 ), and cane cutters (−5·0 ml/min/1·73 m 2 ), as compared to factory workers. The number of years employed at the company was negatively associated with eGFR. Fewer than 5% of workers had albumin-to-creatinine ratio (ACR) >30 mg/g. Conclusions: The decline in kidney function during the harvest and the differences by job category and employment duration provide evidence that one or more risk factors of CKD are occupational.